2021
DOI: 10.1200/jco.21.00920
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Adjusted Etoposide, Doxorubicin, and Cyclophosphamide With Vincristine and Prednisone Plus Rituximab Therapy in Children and Adolescents With Primary Mediastinal B-Cell Lymphoma: A Multicenter Phase II Trial

Abstract: PURPOSE A dose-adjusted etoposide, doxorubicin, and cyclophosphamide with vincristine and prednisone plus rituximab (DA-EPOCH-R) regimen has been shown to deliver excellent survival for adults with primary mediastinal large B-cell lymphoma (PMLBL) without the use of radiotherapy. No international prospective evaluation of this regimen has previously been reported in children and adolescents. PATIENTS AND METHODS We conducted an international single-arm phase II trial involving patients younger than age 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 16 publications
(32 reference statements)
0
20
1
Order By: Relevance
“…These excellent results contrast with the results recently published with DA-EPOCH-R in 46 children and adolescents included in the international phase 2 Inter B-NHL-ritux 2010 study 7 (Table 4). Although the characteristics of the patients included in this study do not differ from those of the phase 2 Inter B-NHL-ritux 2010, 12 disease-related events were observed in the phase 2, with 4-year EFS and OS of 69.6% (95%CI 55.2%-80.9%) and 84.8% (95%CI 71.8%-92.4%), respectively, and 3 (6.5%) parenchymal central nervous system relapses.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…These excellent results contrast with the results recently published with DA-EPOCH-R in 46 children and adolescents included in the international phase 2 Inter B-NHL-ritux 2010 study 7 (Table 4). Although the characteristics of the patients included in this study do not differ from those of the phase 2 Inter B-NHL-ritux 2010, 12 disease-related events were observed in the phase 2, with 4-year EFS and OS of 69.6% (95%CI 55.2%-80.9%) and 84.8% (95%CI 71.8%-92.4%), respectively, and 3 (6.5%) parenchymal central nervous system relapses.…”
Section: Discussioncontrasting
confidence: 96%
“… 21 However, management of long-term toxicity is also very important in this young population. The risks for significant long-term sequelae are relatively modest using LMB chemotherapy backbone 22 and the total cumulative dose of doxorubicin is limited and of 240 mg/m 2 with the LMB B/C-modified combination (favorably compared with the DA-EPOCH-R in the Inter-B-NHL ritux 2010 study where 72% of patients received ≥300 mg/m 2 doxorubicin and 24% ≥350 mg/m 2 ) 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2019 study by Giulino-Roth et al [ 78 ] of adult and pediatric patients with PMLBCL, patients who received DA-EPOCH-R had a 3-year EFS rate of nearly 86% and an OS rate of 95%; however, more children than adults developed thrombosis (46% vs. 23%, respectively). In contrast, a more recent phase 2 trial by Burke et al [ 79 ] involving only pediatric (<18 years old) patients with PMLBCL demonstrated that treatment with DA-EPOCH-R did not confer better EFS or OS (70% and 85%, respectively) compared to control treatment which had similar rates. This international study also compared its results with historical survival rates from the FAB/LMB 96 study.…”
Section: Conventional Treatment Of Nhl In Children and Adolescentsmentioning
confidence: 90%
“…We have discussed this in our Discussion and suggested that DA-EPOCH without rituximab may be less effective than the historical pediatric regimens. 2…”
mentioning
confidence: 99%